Penerapan Arsitektur Metafora pada Pasar Festival Industri Kreatif di Kabupaten Klaten - Rizky M, Hadinar; Musyawaroh, Musyawaroh; Triratma, Bambang (ARSITEKTURA, 2017)
Klaten Regency is located between big tourism cities, such as Surakarta and Yogyakarta. Klaten has its own potential of tourism and creative industries. At the other hand, the facility to support the development of creative industries in Klaten is not sufficient. The purpose of this design is to build a building that have complete facilities for creative industries sectors such as culinary, craft, fashion, music and performing art and not just for selling the products to costumer but also for the developing local creative micro to middle scope businessman in Klaten too, then the product could be developed dan known in national and international range. Using metaphor from one of the best and unique product of Klaten and response of the condition around the site would be a representation of iconic shape of Klaten Regency that would give a synergic interaction and could give a good response with the condition around the site. Keywords: Architecture, Festival marketplace, Creative industry, Metaphor